Islamic Teaching and Values in Boat deployment Kenduri in Deluk Village, Bengkalis District - Meliza Deluk; Wan Muhammad Fariq (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2023)
This study is conducted because numerous people who live in Deluk Village do not comprehend the Islamic values entitled to the boat deployment tradition that has existed for years. Besides, there are yet concrete explanations regarding the benefits and Islamic teachings in the tradition which resulted in different perspectives on this ritual. This investigation aims to comprehend the procedure of boat deployment and understand the Islamic values behind such a tradition. A descriptive qualitative method was employed in this study by commencing observation, interview, and documentation. The finding suggests boat deployment tradition in Deluk Village was a custom and tradition before fishermen started to use the boat for fishing activities. Such tradition has been inherited from generation to generation and still exists till the present time. The results showed that the tradition of kenduri turun kapal pompong carried out by the people of Deluk Village is a custom or habit. This tradition is hereditary and still exists today. The process of carrying out the kenduri tradition of disembarking the pompong ship begins with the preparation of the ceremony, praying together, followed by eating kenduri, tepung tawar, and ending with the lowering of the pompong ship into the sea. The Islamic education values contained in the implementation of the kenduri pompong tradition are the value of tawhid (faith), the value of worship, moral values, and social values.